(untitled) (Research, Society and Development, 2021)
In the Microregion of Campos de Lages, Santa Catarina, the edaphoclimate conditions, associated with the typical vegetation of this region may particularize the foraging behavior of leaf-cutting ants Atta sexdens piriventris, unlike those already reported for other locations. This work aimed to study the bio-ecology of foraging A. sexdens piriventris naturally occurring in the Microregion of Campos de Lages. Thus, anthills of the species A. sexdens piriventris were randomly located, through morphological characteristics of the individuals, and the appearance with the appearance of superficial tilled soil of the anthills. In each selected anthill, a survey of the preferred plant species for foraging was carried out. Samples of the foraged plant species or vegetative parts were herborized and later classified and identified. The edaphoclimatic characteristics of the Campos de Lages Microregion, particularize the foraging and nesting behavior presented by leaf-cutting ants A. sexdens piriventris. 68 species of plants were identified, distributed in 27 botanical families, among those used for foraging. Plants from the Poaceae and Asteraceae families were the most used in the foraging by ants A. sexdens piriventris, with Baccharis trimera (Asteraceae) being the most foraged. Anthilles A. sexdens piriventris were present preferentially in the edge area of ​​environments.